Electrophysiolocical investigation of hemifacial spasm: F-waves and abnormal muscle responses - (:unkn) unknown (My University, 1999)
Objective: The aim of this study was to investigate the mechanism of hemifacial spasm pathophysiologically. Methods: Patients with hemifacial spasm underwent an electrophysiological study of F-wave parameters of the facial nerves on the spasm side. F/M amplitude ratios, F duration and F frequency of appearance and the presence of abnormal muscle response (AMR) were compared with the asymptomatic side of the face which served as a control group. Results: Enhancement of F-wave parameters were observed on the spasm side and AMR was present in all cases on the spasm side whereas it was absent on the other side. Conclusions: Electrophysiological findings suggest the hyperexcitability of facial motor nucleus in hemifacial spasm.
Keywords: F-wave; Facial motor nucleus; Hemifacial spasm; Hyperexcitability